Column versus batch methods for measuring PFOS and PFOA sorption to geomedia. (1st January 2021) - Van Glubt, Sarah; Brusseau, Mark L.; Yan, Ni; Huang, Dandan; Khan, Naima; Carroll, Kenneth C.
Abstract: The objective of this study is to compare the consistency between column and batch experiment methods for measuring solid-phase sorption coefficients and isotherms for per and polyfluoroalkyl substances (PFAS). Perfluorooctane sulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) are used as representative PFAS, and experiments are conducted with three natural porous media with differing geochemical properties. Column-derived sorption isotherms are generated by conducting multiple experiments with different input concentrations (multi-C0 method) or employing elution-front integration wherein the entire isotherm is determined from a single breakthrough curve (BTC) elution front. The isotherms generated with the multi-C0 column method compared remarkably well to the batch isotherms over an aqueous concentration range of 3–4 orders of magnitude. Specifically, the 95% confidence intervals for the individual isotherm variables overlapped, producing statistically identical regressions. The elution-front integration isotherms generally agreed with the batch isotherms, but exhibited noise and systematic deviation at lower concentrations in some cases. All data sets were well described by the Freundlich isotherm model. Freundlich N values ranged from 0.75 to 0.81 for PFOS and was 0.87 for PFOA and are consistent with values reported in the literature for different geomedia. The results of this study indicate that column and batch experiments can measure consistent sorption isotherms and sorption coefficients for PFOS and PFOA when robust experimental setup and data analysis are implemented. Graphical abstract: Image 1 Highlights: PFAS adsorption isotherms determined from column and batch methods match very well. The isotherms are consistent for adsorption of PFOS and PFOA by three geomedia. Retardation factors determined from column data with different methods are similar. Abstract : Column and batch methods produced consistent isotherms for PFOS and PFOA sorption by three geomedia of differing geochemical properties.